Re-thinking 'harm' in relation to children's work: a 'situated, ' multi-disciplinary perspective. (3rd July 2022) - Maconachie, Roy; Howard, Neil; Bock, Rosilin
ABSTRACT: The UN calls for the elimination of child labour by 2030, and its 'worst forms' by 2025. Implicit in this mandate is the assumption that children's work is harmful, yet no coherent theory of harm exists within the child labour field. Moreover, evidence suggests that simply removing children from supposedly harmful work is often damaging. This paper explores how harm may be understood and identified in the context of children's work. It reviews and synthesises literature from multiple disciplines, pointing towards a more situated and nuanced approach to harm that incorporates both 'subjective' and 'objective' dimensions.